THE EXISTENCE OF CUSTOMARY LAND OF THE KAUM AS COMMUNAL PROPERTY RIGHTS POST-CERTIFICATION IN LIMA PULUH KOTA REGENCY - Putri, Vikkania Rahmi Andika; Nurdin, Zefrizal; Najmi, Najmi (JCH (Jurnal Cendekia Hukum), 2024)
This research is motivated by the fact that the existence of land is essential for human life; the land is not only understood as an economic resource, a place to live, and a place for the grave, but it is also something sacred, especially for the Minangkabau people, especially communal land which is considered to have magical religious value. The existence of communal land as communal property, especially in Fifty Regency Cities, is decreasing daily. Both in terms of quality and quantity, in terms of quality, with the certification of these people's customary rights, in the perspective of Minangkabau customary law, the quality will decrease because it will be easily transferred or switched to other parties, either by purchasing and selling or used as collateral at the bank. Regarding quantity, the certification of customary rights will make the land of high value and easy to buy and sell or transfer to other parties. Besides, Minangkabau customary law prohibits buying and selling of customary land; this is stated in the old custom saying or kato adat, "Jua indak makan bali, gadai indak dimakan sando," which means that customary land cannot be bought and sold. Its ownership is transferred to parties outside the legal community association.